Kinesiological Factors in Vertical Jump Performance: Differences Among Individuals - Aragón Vargas, Luis Fernando (1997)
The purpose of this study was to investigate the kinesiological factors that distinguish good jumpers from poor ones, in an attempt to understand the critical factors in vertical jump performance (VJP). Fifty-two normal, physically active male college students each performed five maximal vertical jumps with arms akimbo. Ground reaction forces and video data were collected during the jumps. Subjects' strength was tested isometrically. Thirty-five potential predictor variables were calculated for statistical modeling by multiple-regression analysis. At the whole-body level of analysis, the best models (which included peak and average mechanical power) accounted for 88% of VJP variation (p < .0005). At the segmental level, the best models accounted for 60% of variation in VJP (p < .0005). Unexpectedly, coordination variables were not related to VJP. These data suggested that VJP was most strongly associated with the mechanical power developed during jump execution.